Transformational Leadership of the School Principal in Improving the Quality of Human Resources at SMP Satu Atap Negeri 14 Sigi - Noprianto (Journal of Education and Teaching Learning, 2026)
Transformational leadership of the principal plays an important role in improving the quality of human resources at SMP Satu Atap Negeri 14 Sigi. Transformational leadership is capable of inspiring, motivating, and encouraging positive change through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This leadership is implemented through the establishment of a clear vision and mission, the provision of motivation and exemplary behavior, the strengthening of a collaborative work culture, and the development of teachers’ competencies through continuous training and guidance. In addition, individualized consideration is given to the needs and potential of each educator and educational staff member. The implementation of transformational leadership has an impact on improving teacher professionalism, increasing the discipline and performance of educational staff, and creating a conducive school climate oriented toward quality improvement. Therefore, the transformational leadership of the principal significantly contributes to enhancing the quality of human resources at SMP Satu Atap Negeri 14 Sigi.